Examining Third-Year Students on Their Behavioral Intention and Use Behavior of DingTalk Learning Platform in Chengdu, China - Jin, Wang (Scholar: Human Sciences, 2024)
Purpose: This study aims to investigate the factors that influence students’ learning behavior in vocational colleges in Chengdu, China, using the DingTalk learning platform for mental health courses. The variables in this conceptual framework are perceived ease of use, perceived usefulness, attitude, self-efficacy, subjective norm, behavioral intention, and use behavior. Research design, data, and methodology: The study was conducted quantitative research to employ a questionnaire as the research instrument. The target group consisted of third-year students (n=500) from three collages with prior experience using the DingTalk Learning Platform in Chengdu, China. In this study, sampling procedures are judgmental, stratified random, and convenience sampling. The main statistical tools employed in this study were confirmatory factor analysis and structural equation modeling. These analyses were used to assess the data quality, validate the proposed model, and examine the influence of key variables. Results: The results show that all hypotheses are supported. Additionally, perceived ease of use has the strongest influence on attitude. Conclusions: Educational institutions and platform developers can enhance third-year students’ behavioral intention and use behavior towards the DingTalk Learning Platform in Chengdu, China. This, in turn, can lead to improved learning experiences, increased engagement, and better academic outcomes for these students.